The Influence of Digital Marketing on Community Perceptions and Health Services in Local Government-Owned Hospitals in Kediri City - Muhammad Roihan Mahesa Putra; Amelindha Vania; Hariyono; Yuly Peristiowati (Universitas STRADA Indonesia, 2025)
Marketing using digital applications is very important and cannot be separated from health service units. In the context of providing health services, a hospital is starting to move towards commercialization. One way to increase the utilization of hospital services and improve public health is to develop marketing management so that more patients come to the hospital to get services. This study aims to analyze the effect of digital marketing on public perception and health services in government hospitals in Kediri City. This study uses a quantitative approach with a descriptive analytical design and cross-sectional method to test the effect of digital marketing on public perception and health services in government hospitals in Kediri City.